The Biological basis of mental health - Blows, William T. (London, United Kingdom : Routledge, 2022)
This book explores the underlying biology and neuroscience associated with mental health and wellbeing. This fully revised fourth edition includes new chapters on behavioural science, and brain-gut and brain-gender connections, as well as expanded content on memory and genetics. Integrating up-to-date pharmacological and genetic research with an understanding of environmental factors that impact on human biology, The Biological Basis of Mental Health covers topics including brain development, neural communication, neurotransmitters and receptors, hormones and behaviour, genetic disorders, pharmacology, substance misuse, anxiety, schizophrenia, depression, epilepsy, subcortical degenerative diseases of the brain, dementia, developmental disorders, and sleep. This unique textbook is an essential read for all healthcare students, practitioners and educators with an interest in mental health and neuroscience
1.Introduction to the brain. -- 2.Brain development -- 3.Neural communication -- 4.Neurotransmitters and receptors -- 5.The brain-body connection: Gut microbiota, immunity and brain gender. -- 6.Hormones -- 7.Behaviour -- 8.Genetics I: Introduction and Autosomes -- 9.Genetics II: Sex chromosomes and gene disorders. -- 10.Pharmacology -- 11.Illicit substance use disorders -- 12.Common substance misuse -- 13.Emotions -- 14.Stress, anxiety and fear. -- 15.Schizophrenia -- 16.Antipsychotic drugs -- 17.Affective disorders -- 18.Antidepressant drugs -- 19. Epilepsy -- 20.Subcortical degenerative disorders of the brain -- 21.Memory and learning -- 22.The ageing brain and dementia -- 23.Communication and developmental disorders -- 24. Sleep.
Includes bibliographical references and index.
Keywords: BIOLOGICAL PSYCHIATRY